The relation between the transaction costs and the co-ordination in the agri-food economy - Horváth, B.; Kósa, C.; Szabó, Gábor G. (Acta Agraria Kaposváriensis, 2001)
In the first part of the paper the basic co-ordination mechanisms are defined. In the agri- food economy system usually two co-ordination forms are well known: market mechanism and bureaucratic co-ordination. The second part of the paper analyses the transaction costs, their characteristics and their role in the agribusiness. Transaction costs are the costs associated with carrying out a transaction on the market. The study presents the main factors for decisions to integrate vertically, the reasons why vertical integration exists and the possibilities to reduce transaction costs. One of the varieties of reducing transaction costs is establishing agricultural co-operative, which is a special kind of transaction and co-ordination form. The study demonstrates the characteristics and the importance of the above mentioned co-operatives in vertical integration.
Keywords: agri-food economy; co-ordination; transaction costs; co-operatives